History and Humans: Study of the Urgency and Position of History in Human Life - Arditya Prayogi; Nasrullah, Riki (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2024)
Humans in their civilization gain insight into human failures and successes through history. In this way, history provides valuable lessons that humans can apply today. Understanding history then allows humans to understand the roots of problems, conflicts and social dynamics that exist in society today. This article aims to review the urgency and position of history in human life. This article was written using a qualitative approach using the literature study method. From the results of the study, it implies that history is not just a legacy. Through history it is hoped that humans can learn and realize that everything is not instantaneous, everything goes through a process so that the future will be better. History has an important meaning for human civilization. This can be seen from the role of history as a basic reference in dealing with life today and predicting life in the future.